Accuracy of Fetal Weight Estimation in Women with Diet Controlled Gestational Diabetes - Husslein, H.; Worda, C.; Leipold, H.; Szalay, Stefan (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: To evaluate whether ultrasound accuracy of estimated fetal weight (EFW) differs in women with diet controlled gestational diabetes mellitus (GDM) compared to nondiabetic pregnant women. Material and Methods: We included 363 patients, 121 patients with diet controlled GDM and 242 patients with a normal oral glucose tolerance test (oGTT). Each case of diet controlled GDM was matched with 2 unaffected controls. All patients were screened/diagnosed for GDM by means of an oGTT. Both groups received ultrasound examination including fetal biometry, using Hadlockʼs Formula, within 7 days to delivery. After birth, gestational age, birthweight and Apgar scores were collected from each newborn. Results: There was a good correlation between EFW and birth weight (coefficient = 0.747, p < 0.001 by Pearson correlation, even after adjustment for glucose status). Regression analyses, including noGDM/GDM, maternal age, maternal body mass index, birth weight and time interval between ultrasound and delivery revealed that only fetal birth weight significantly influences weight difference between ultrasound EFW and actual birth weight at term. Conclusion: Our data suggests that ultrasound accuracy of EFW using Hadlockʼs Formula at term does not differ in women with diet controlled GDM compared to women with normal glucose tolerance.
Keywords: ultrasound; estimated fetal weight; gestational diabetes